2018
DOI: 10.1080/15384101.2018.1496742
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of human multiple myeloma cells with bortezomib and doxorubicin alters the interactome of 20S proteasomes

Abstract: BD: bortezomib/doxorubicin treatment; CDK: cyclin-dependent kinases; CHCA: α-cyanohydroxycinnamic acid; IDP: intrinsically disordered proteins; IDR: intrinsically disordered regions; IPG: immobilized pI gradient; MALDI TOF/TOF: matrix-assisted laser desorption/ionization time-of-flight tandem mass-spectrometry; MM: multiple myeloma; ODC: ornithine decarboxylase; PI: proteasomal inhibitors; PSMA: alpha-type 20S proteasome subunits; PTMs: post-translational modifications; SDS-PAGE: sodium dodecylsulphate polyacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The P20S β5 subunit is the known chymotrypsin-like catalytic subunit for SUC-LLVY-AMC [48]. The P20S α3 subunit is a cornerstone structural subunit that interacts with many different proteins and functions as a putative core particle gatekeeper [49]. The P20S α3 subunit also has a role in RNA metabolism, cell death, and cell cycle control [50,51], which could be important to oligodendrocytes in immature white matter after HI [23,34].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The P20S β5 subunit is the known chymotrypsin-like catalytic subunit for SUC-LLVY-AMC [48]. The P20S α3 subunit is a cornerstone structural subunit that interacts with many different proteins and functions as a putative core particle gatekeeper [49]. The P20S α3 subunit also has a role in RNA metabolism, cell death, and cell cycle control [50,51], which could be important to oligodendrocytes in immature white matter after HI [23,34].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…For MALDI TOF/TOF (tandem time-of-flight mass spectrometry (MS/MS) mass spectrometry, the trypsin digested (Trypsin Gold, Madison, WI, USA) protein samples were analyzed with an AB Sciex TOF/TOF 5800 System (SCIEX, Darmstadt, Germany) instrument operated in the positive ion mode [ 24 ]. The MALDI stage was set to continuous motion mode.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently reported that the C-terminal region of the proteasome α7 subunit (or PSMA3) could play the role of substrate receptor for IDPs. 22,34 Thus, we hypothesized that even blocked by epoxomicin, the 20S proteasome could immobilize part of the galectin-3 pool, through interaction of the lectin N-terminal disordered region with the C-terminal region of proteasome α7 subunit, and therefore could impair hemagglutination (Figure 8B). To test this hypothesis, 20S proteasome was blocked by epoxomicin and incubated with biotinylated galectin-3 before loading onto a sucrose gradient.…”
Section: Functional Features Of Secreted Proteasome Collected From Ce...mentioning
confidence: 99%